Root hairs: development, growth and evolution at the plant-soil interface - Datta, S; Kim, C; Pernas, M; Pires, N; Proust, H; Tam, T; Vijayakumar, P; Dolan, L (2011)
Root hairs are tip-growing extensions from root epidermal cells that play important roles in nutrient uptake and in plant-soil interactions. In this review, we discuss the major environmental, physiological and genetic factors that regulate the differentiation and growth of root hairs in angiosperms. Root hair cells are arranged in a number of different patterns in the root epidermis of different species. In Arabidopsis (Arabidopsis thaliana L.), a striped pattern of hair and non-hair files is generated by an intercellular gene regulatory network that involves feedback loops and protein movement between neighbouring cells. The growth of root hairs can be broadly divided into an initiation phase, where site selection and bulge formation take place, and an elongation phase. The initiation phase is regulated by different transcription factors, GTPases and cell wall modification enzymes. During the elongation phase root hairs grow by tip growth, a type of polarised cell expansion that is restricted to the growing apex. Root hair elongation is characterized by a strong polarisation of the cytoskeleton, active cell wall modifications and dynamic ion movements. Finally, we discuss the functional and genetic similarities between the root hairs of angiosperms and the rhizoids of bryophytes and ferns. © 2011 Springer Science+Business Media B.V.